Analysis of learning styles in terms of knowledge, skills and attitudes - Abdul Halim; Adinda Wirda; Yusrizal Yusrizal (Universitas PGRI Kanjuruhan Malang, 2022)
The purpose of this study is to determine the domains of knowledge, skills and attitudes of students which are dominantly influenced by learning styles. The approach used is quantitative research with a correlation method in the form of a survey on 71 high school students in the Aceh Tengah area. The data collection instrument used a questionnaire for learning style data and documentation study for student learning outcomes data. The results of data analysis using descriptive and inferential statistics show that there is a significant relationship between learning styles and knowledge, skills and attitudes with an average contribution of 17.67%, 14.77% and 72.4% respectively. Based on the types of learning styles selected in this study, the visual learning style is more highly related to students' knowledge, skills and attitudes. The conclusion from the results of this study is that teachers as educators need to know and understand the characteristics of each student's learning style, so as to be able to place students in the right position during the learning process.